Microfluidic supercritical antisolvent continuous processing and direct spray-coating of poly(3-hexylthiophene) nanoparticles for OFET devices. Issue 6 (3rd November 2014) - Couto, Ricardo; Chambon, Sylvain; Aymonier, Cyril; Mignard, Emmanuel; Pavageau, Bertrand; Erriguible, Arnaud; Marre, Samuel
Abstract : We report for the first time the use of a microfluidic supercritical antisolvent process (μSAS) to synthesize semiconducting polymer nanoparticles (NPs) of poly(3-hexylthiophene) (P3HT). Abstract : We report for the first time the use of a microfluidic supercritical antisolvent process (μSAS) to synthesize semiconducting polymer nanoparticles (NPs) of poly(3-hexylthiophene) (P3HT). Solvent-free P3HT NPs with average diameters as small as 36 ± 8 nm are obtained. They are continuously spray-coated on substrates to fabricate OFET devices, demonstrating hole mobility through the nanoparticle film equivalent to that of conventional spin-coated P3HT.